Perancangan Strategi Dalam Menciptakan Ikon Baru Kota Garut Pada Sektor Industri Kuliner - Ikhwana, Andri; Efendi, Kurniawan (Jurnal Kalibrasi, 2025)
This study aims to design a strategy for developing the culinary industry to create a new icon for the city of Garut. Using a mixed-methods approach, the research employs factor analysis to identify key variables influencing culinary businesses, followed by a SOAR (Strengths, Opportunities, Aspirations, and Results) analysis to formulate strategies based on strengths and opportunities.The findings reveal five main factors driving culinary industry development: local cultural and traditional values, promotion and collaboration, digitalization and product standardization, product innovation and quality, and quality service. Effective strategies to establish a culinary icon include product innovation, utilizing digital technology in marketing, and strengthening collaboration with local communities and the government.The study implies the importance of policy support in enhancing the competitiveness of Garut’s culinary industry through digital promotion and product standardization.